1998
DOI: 10.1007/s003390051178
|View full text |Cite
|
Sign up to set email alerts
|

A study of the spatial variation of electric field in highly resistive metal films by scanning tunneling potentiometry

Abstract: Electronic transport in highly resistive (but metallic) thin platinum films (≈ 10 nm) deposited by electronbeam evaporation has been studied by scanning tunneling microscopy and scanning tunneling potentiometry (STP). The films have an average grain size of ≈ 10 nm. On this scale transport through the film is very inhomogeneous. Scattering from grain boundaries (GBs) results in large variations in the local potential resulting in fields as high as 10 4 -10 5 V/cm located near the GB. The reflection coefficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…F was experimentally determined to be equal to 0.5±0.7 for platinum, [37] and we used 0.6. With r bulk = 10.7 lX cm, we obtained perfect agreement with experimental data for crystallite dimensions greater than 10 nm, irrespective of all the experimental conditions used, but below this value the resistivity rapidly increases without obeying the theoretical trend, therefore we applied a corrective factor, k/(2 D), to values under 10 nm.…”
Section: Methodsmentioning
confidence: 99%
“…F was experimentally determined to be equal to 0.5±0.7 for platinum, [37] and we used 0.6. With r bulk = 10.7 lX cm, we obtained perfect agreement with experimental data for crystallite dimensions greater than 10 nm, irrespective of all the experimental conditions used, but below this value the resistivity rapidly increases without obeying the theoretical trend, therefore we applied a corrective factor, k/(2 D), to values under 10 nm.…”
Section: Methodsmentioning
confidence: 99%
“…To obtaining STM data in the ac mode, the modulation voltage is added to the sample bias voltage, and in order to pick up the resulting ac component in the tunneling current, we inserted an absolute amplifier before the STM feedback, instead of a lock-in amplifier, which is often used to extract an ac component, because of its fast response and simplicity. 9) Since the frequency of the modulation is higher than the STM feedback response, the averaged absolute current, which is proportional to the differential tunneling conductance, is utilized for the tip height control. The lower part of Fig.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…As one of the SPM techniques, scanning tunneling potentiometry (STP) uniquely provides nanoscale mappings of the potential landscape induced by current flow in thin films or surface layers, and has been used on various materials. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] It was first invented by Muralt and Pohl in 1986, 1) and later Kirtley et al demonstrated its high performance by visualizing potential drops at grain boundaries in a AuPd film, 3) which clearly indicated the finite electrical resistance there. A recent STP work on graphene also elucidated the potential drops at grain boundaries.…”
Section: Introductionmentioning
confidence: 99%
“…The reflection coefficients for various metallic NFs have a large span. Taking Pt NFs as an example, the reflection coefficient ranges from 0.15 to about 0.8 [7][8][9].…”
Section: Introductionmentioning
confidence: 99%